Pendampingan Pemilihan Jajanan Halālan Tayyiban bagi Kesehatan Anak Sekolah Dasar di SD Muhammadiyah 01 Wuled - Risdiani Risdiani; Yuni Sandra Pratiwi; Warsiyah Warsiyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
This community service activity aims to teach students about understanding and the importance of choosing halālan tayyiban snack foods to increase child immunity. This dedication activity was held at this service activity held at Muhammadiyah Elementary School 01 Wuled, Tirto, Pekalongan. Before the socialization of respondents filled the pretest first, and after the socialization, served the post-test when data was done by testing the t-test paired sample. Students' knowledge about the importance of choosing food snacks for the thesis increases immunity through this program.